К вопросу о специфике специальнонаучной картины мира исторической дисциплины - Кравченко, И. С. (ХНУРЭ, 2012)
In this paper the possibility of application of the notion of 'special scientific picture of the world in the historical discipline is discussed. The disciplinary ontology of historical science, as well as of natural sciences, has its ideal objects. But in historical science disciplinary ontology loses the ontological status and becomes a subjective historian's ≪image of reality≫